UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PENJASKES MELALUI METODE PEMBELAJARAN DRILL PADA SISWA KELAS III SDN 27 PASAMAN - zulhasmi zulhasmi (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACT Based on student learning outcomes Class VIII.I SDN 27Pasaman in Penjaskes subjects found that student learning outcomes in subjects Penjaskes still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in subjects Penjaskes Practice Combination of basic motion of roads, running and jump with a good combination in simple games, and the value of cooperation, tolerance, honesty, responsibility and appreciate the opponent or Self through Drill Learning Method in Class III SDN 27 Pasaman Pasaman Barat Regency. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 35 students of Class III SDN 27 Pasaman. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that Drill Learning Method can improve student learning outcomes in subjects Penjaskes Practice Combination of basic motion of roads, run and jump with a good combination in simple games, and cooperation values, tolerance, honesty, responsibility Answer and appreciate the opponent or self of SDN 27 Pasaman. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 55.14 (Enough) increased to 85.31 (Good) with an increase of 30.17%. Keywords: Learning Outcomes, Penjaskes, Drill Learning Method